2021
DOI: 10.1590/1809-4430-eng.agric.v41n4p427-437/2021
|View full text |Cite
|
Sign up to set email alerts
|

Trailer Heat Zones and Their Relation to Heat Stress in Pig Transport

Abstract: This study evaluates the dynamics of heat zones in the load and its relationship with the stress of pigs during transport. Four journeys of 170 km were monitored, recording the physiological variables of 192 animals (48 per journey), namely rectal temperature (RT), body temperature (BT), respiratory rate (RR), blood lactate concentrations and salivary cortisol. Heat zones and ventilation patterns were characterized by the spatial variability of the enthalpy and the Computational Fluid Dynamics of the load. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…These findings were confirmed by Machado et al ( 117 ) in their study of 192 hogs transported for 170 km, where they recorded rectal and ocular temperatures (with a fixed distance of 0.50 m between the animal and the observer), saliva cortisol levels, respiratory rate, and lactate levels, while also comparing the influence of the upper and lower transport levels inside the vehicle. They observed that the average post-transport temperature in the animals at the upper level was higher than those below (upper = 39.9°C, lower = 38.1°C; P = 0.022).…”
Section: Infrared Thermography (Irt) As a Tool To Evaluate The Therma...supporting
confidence: 68%
“…These findings were confirmed by Machado et al ( 117 ) in their study of 192 hogs transported for 170 km, where they recorded rectal and ocular temperatures (with a fixed distance of 0.50 m between the animal and the observer), saliva cortisol levels, respiratory rate, and lactate levels, while also comparing the influence of the upper and lower transport levels inside the vehicle. They observed that the average post-transport temperature in the animals at the upper level was higher than those below (upper = 39.9°C, lower = 38.1°C; P = 0.022).…”
Section: Infrared Thermography (Irt) As a Tool To Evaluate The Therma...supporting
confidence: 68%
“…Environmental conditions and trailer compartment locations can impact pig comfort and welfare. Thermal variations between trailer compartments occur because of the lack of ventilation due to trailer pressure distribution variation during transportation (Machado et al, 2021a;Machado et al, 2021b). In the current study and during morning LOD, the fore section had 1.5°C-greater ambient and delta-temperatures than the averages of the center and aft sections.…”
Section: Discussionmentioning
confidence: 50%
“…Morris et al (2021) observed similar results where the bottom decks had a greater ambient temperature and relative humidity by 2.7°C and 4.1%, respectively, during winter. (Machado et al 2021a;2021b) stated that bottom decks have greater temperatures due to thermal heat core formation resulting in a reduced heat removal rate. Generally, the trailer's top decks have favorable ventilation conditions for pigs during transportation, but Machado et al (2021a) stated that pigs transported in top decks were more susceptible to physical stress related to direct solar exposure, which could add to stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though enthalpy has been reported in some studies in relation to the quantification of heat stress in pigs during transport (e.g. Dalla Costa et al, 2019;Machado et al, 2021;Miranda-de la Lama et al, 2021), at the present stage, it is considered that too few data are available to be able to give recommendations based on enthalpy. Thus, this Scientific Opinion focuses on the temperature immediately surrounding the pigs and measures of humidity.…”
Section: D) Thermal Heat Indicesmentioning
confidence: 96%